Mediating Effect of Filial Piety Between the Elderly’s Family Resource Contribution and Their Family Power: Evidence from China - Liu, Xin; Bai, Shuying (Frontiers in Psychology, 2022)
With the development of rationalism, although the concept of filial piety is still an important factor affecting family relations, its rules have changed. Based on the resource theory and by measuring family status via the role played in family decision-making (FDM), this study explored the mediating role of filial piety norms between elderly’s family resource contributions and family status in intergenerational cohabitation families in M City, China. Using stratified sampling method, 1200 elderly people were recruited for data collection. Multiple linear regression analysis and bootstrap methods were used for testing. The results show that: (1) the elderly still have some FDM in Chinese intergenerational cohabitation families, and the family power of elderly males is still higher than that of elderly females, indicating that the influence of traditional patriarchal norms still exist in the family.(2) Filial piety culture mediates between the elderly's relative economic income (relative to their adult children) and their family power, and also mediates the relationship of the elderly's relative educational level (relative to their adult children) and their family power. It shows that the resources of the elderly relative to their children affect the filial piety of their adult children, and then affect the FDM of the elderly. This shows that filial piety in modern society is a kind of ‘reciprocal filial piety’ based on rationalism. The study is meaningful theoretically and practically.